Pengaruh Electroplating Krom Terhadap Ketebalan Dan Kekerasan Lapisan Pada Jari-Jari Sepeda Motor Yang Telah Di-Electroplating Nikel: Effect of Chrome Electroplating on The Thickness and Hardness of The Coating on The Spokes of a Motorcycle That Has Been Electroplated With Nickel - Fauzan Fikrat Winata; Agus Fikri; M Mujirudin (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2022)
The purpose of this study was to determine the effect of chrome electroplating on the thickness and hardness of the spokes of a motorcycle wich has been electroplating nikel. This research was conducted in the laboratory room of PT. Enkei Indonesia and PT. Murni Cahaya Pratama Bekasi, West Java, Indonesia between January - March 2021 using nickel-chrome electroplating, the spokes of the motorcycle are made of st37 steel which has been electroplated with nickel, then electroplated with chrome. The parameters of the research were 4A, 6A, and 8A immersion currents. The tests carried out are thickness, hardness, macro structure and micro structure. The results showed that the effect of the strong current on the electroplating coating resulted in the highest value of thickness with an average of 26.77µm, the microstructure was corrosion resistant and non-magnetic, the macro structure showed the results of black spots indicating defects such as porosity and the highest value of hardness with an average 4H